Improving Warehouse Operations in Cargo Companies through Agile-based Warehouse Management System - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
This research addresses the complex problem of warehouse operations of freight forwarders, which often face challenges related to stock management, dispatch, and distribution of goods. This research proposes an Agile approach as a potential solution by looking at traditional warehouse management systems that must be more responsive to changing customer demands and dynamic market conditions. Literature analysis and case studies show that implementing an Agile-based warehouse management system can improve operational efficiency and flexibility. By applying Agile principles, companies can be more responsive to change, increase team collaboration, and improve the process of stock management, dispensing, and distribution of goods. This research provides a better understanding of the relevance of Agile principles in managing a freight forwarder's warehouse operations while highlighting the potential advantages that can be gained through implementing an Agile-based warehouse management system, as well as the challenges that need to be overcome in the process. As such, this research provides a strong foundation for recommending the use of Agile-based warehouse management systems to improve operational efficiency and effectiveness in the freight forwarding industry.